Felix Siauw’s Digital Da’wah Strategy in Strengthening Indonesian People’s Solidarity for Palestinian Independence - Lalu Ahmad Zaenuri (Asian Journal of Islamic Studies and Da'wah, 2026)
This article analyzes Felix Siauw’s digital da‘wah strategy in building public solidarity for Palestinian independence in Indonesia. Moving beyond the assumption that digital da‘wah merely transfers religious lectures into online spaces, the study conceptualizes it as a strategic communication practice that frames geopolitical issues, intensifies affect, and directs cross-platform collective action. The research employed an interpretive qualitative approach with a cross-platform netnography design. The corpus consisted of Palestine-themed public content within Felix Siauw’s digital ecosystem, with primary emphasis on YouTube and Telegram, while Instagram, TikTok, and X served as complementary platforms. Data were collected through systematic manual archiving of uploads, captions, videos, engagement metrics, comments, and campaign trails, and were analyzed using hybrid coding, thematic analysis, and multimodal discourse analysis. The findings show that Palestine is constructed through a differentiated platform ecosystem in which YouTube deepens narrative and interpretive authority, while Telegram functions to amplify, archive, and direct participation. Felix Siauw’s messages sacralize Palestine through references to Jerusalem, Al-Aqsa, and Islamic history, thereby presenting a distant geopolitical conflict as an immediate moral and religious obligation for Indonesian Muslims. This framing is further reinforced through affective intensification in the form of suffering, empathy, moral anger, and urgency, which together constitute a moral public grounded in the imagination of the ummah and shared responsibility. The study also identifies multilayered solidarity outcomes, ranging from symbolic expression and discursive reproduction to donations, boycott support, and offline participation. This article concludes that Felix Siauw’s Palestine-oriented da‘wah represents a form of public solidarity mediated by platformed religious authority and capable of moving audiences from expression to action in Indonesia’s digital public sphere in a communicative, structured, cross-platform, and sustained manner during moments of crisis. The study contributes to the understanding of how digital religious communication mobilizes solidarity by linking platform logic, affective framing, and collective action in contemporary Muslim public life.